ROS and diseases: role in metabolism and energy supply - Yang, Shenshu; Lian, Gaojian (Molecular and cellular biochemistry, 2020)
Researches dedicated to reactive oxygen species (ROS) had been performed for decades, yet the outcomes remain controversial. With the relentless effort of studies, researchers have explored the role of ROS in biosystem and various diseases. ROS are beneficial for biosystem presenting as signalling molecules and enhancing immunologic defence. However, they also have harmful effects such as causing tissue and organ damages. The results are controversial in studies focusing on ROS and ROS-related diseases by regulating ROS with inhibitors or promotors. These competing results hindered the process for further investigation of the specific mechanisms lying behind. The opinions presented in this review interpret the researches of ROS from a different dimension that might explain the competing results of ROS introduced so far from a broader perspective. This review brings a different thinking to researchers, with the neglected features and potentials of ROS, to relate their works with ROS and to explore the mechanisms between their subject and ROS.